Retained Urethral Catheter Secondary to Placement in Proximal Ureter - Thomas B. McGregor; Rajan Sharda (Case Reports in Urology)
We present an unusual complication secondary to indwelling urethral catheter placement. Routine catheter placement by the obstetrics team in a postpartum female leads to retention of the catheter and inability of its removal by both the obstetrics and urology teams. Although a retained urinary catheter is relatively common, inability to remove a catheter secondary to placement inadvertently into a ureter is extremely rare. In this paper we will discuss the options in removing a retained catheter and present our case of a retained catheter secondary to placement within the right proximal ureter.